Gelatinous zooplankton (ctenophores, salps and medusae): an important food resource of fishes in the temperate SW Atlantic Ocean. Issue 6 (3rd July 2017) - Diaz Briz, Luciana; Sánchez, Felisa; Marí, Noemí; Mianzan, Hermes; Genzano, Gabriel
ABSTRACT: This study quantifies the occurrence of gelatinous zooplankton in the stomach contents of fishes from the southwest Atlantic Ocean (33°–55°S). More than 69, 000 fish stomachs belonging to 107 species were examined. A total of 39 fishes were documented as consumers of gelatinous zooplankton, 23 of which were newly discovered. Three gelatinous organism consumption categories are recognized: (1) very frequent consumers (10 species, six of which were exclusive); frequent consumers (five species); and occasional consumers (26 species). Three types of gelatinous prey (ctenophores, salps and medusae) were found in the stomach contents of fishes. Ctenophores were consumed at high levels across almost the entire continental shelves of Argentina and Uruguay. Salps were frequent prey on the slope and southern shelf. In contrast, medusae were consumed in coastal areas, slopes and the southern shelf. Classification methods (group average sorting of the Bray–Curtis similarity measures based on log ( X  + 1)-transformed percentage data) determined six areas where fishes predated on gelatinous organisms. SIMPER (similarity percentages) analysis determined which fishes contributed more to the consumption of gelatinous organisms. Results revealed that two fish species ( Stromateus brasiliensis and Squalus acanthias ) had high gelatinous zooplankton predation rates throughout the entire study area, while another six species ( Patagonotothen ramsayi, Helicolenus dactylopterus lahillei, Macrourus holotrachys, Merluccius hubbsi, Schroederichthys bivius, and Macruronus magellanicus ), while widely distributed, seemed to have specific areas where consumption occurred. This study not only provides new knowledge about the importance of gelatinous zooplankton in the diet of numerous fishes, but might also be valuable for planning and managing local fisheries.